Association of coronary artery calcium score groups with qualitative and quantitatively assessed adverse plaque. (14th October 2021) - Osborne-Grinter, M; Kwiecinski, J; Cadet, S; Adamson, P D; Mills, N L; Roditi, G; Van Beek, E J R; Shaw, L J; Nicol, E D; Berman, D; Slomka, P J; Newby, D E; et al.
Abstract: Introduction: Coronary artery calcification is a marker of cardiovascular risk, but its association with qualitatively and quantitatively assessed plaque subtypes on coronary computed tomography (CT) angiography (CCTA) is unknown. Methods: In this post-hoc analysis, CT images and clinical outcomes were assessed in SCOT-HEART trial participants. Agatston coronary artery calcium score (CACS) was measured on non-contrast CT and was stratified as zero (0 Agatston units, AU), minimal (1 to 9AU), low (10 to 99AU), moderate (100 to 399AU), high (400 to 999AU) and very high (≥1000AU). Adverse plaques were investigated with qualitative (visual categorisation of positive remodelling, low-attenuation plaque, spotty calcification, napkin ring sign) and quantitative (calcified, non-calcified, low-attenuation and total plaque burden) methods. Results: Images of 1769 patients were assessed (mean age 58±9 years, 56% male, median Agatston score 21 [interquartile range 0 to 230] AU). Of these 36% had a zero, 9% minimal, 20% low, 17% moderate, 10% high and 8% very high CACS. Amongst patients with a zero CACS, 14% had nonobstructive disease, 2% had obstructive disease, 2% had visually assessed adverse plaques and 13% had quantitative low-attenuation plaque (LAP) burden >4% (Figure 1). Non-calcified and low-attenuation plaque burden increased between patients with zero, minimal and low CACS (p<0.001), but there was no difference between those with medium, high and very high CACS. Over a median follow-up of 4.8 [4.1 to 5.7] years, fatal or non-fatal myocardial infarction occurred in 41 patients, 10% of whom had zero CACS. CACS ≥1000AU (Hazard ratio (HR) 4.55 [1.20 to 17.3], p=0.026) and low-attenuation plaque burden (HR 1.74 [1.19 to 2.54], p=0.004) were the only predictors of myocardial infarction, independent of obstructive disease and cardiovascular risk score. Figure 2 shows example CCTA images in a patient with zero CACS, non-calcified plaque (red), low attenuation plaque (orange) burden >4% and obstructive disease in the left anterior descending coronary artery. Conclusions: In patients with stable chest pain, a zero CACS is associated with a good prognosis, but 1 in 6 have coronary artery disease, including the presence of adverse plaques. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): British Heart Foundation, National Institute of Health/National Heart, Lung, and Blood Institute